A Clinical Study to Evaluate Effect of Sarjarasa Malahara Lepa (Sarjarasa Ointment) in the Management of Padadari (Crack Heel) - B Waddar, Sujata; Waddar, Shridhar B; Chalageri, Chaitra C (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Ayurveda (science of life) considers lifestyle and cosmetic aspects. Change in lifestyle like walking excessively and wearing improper footwear’s/barefoot walkers, and expose to cold water, and dirt leads to appearance of symptoms such as dryness of feet, cracks, flaring patches, itchy skin, and pain in the palms and soles. Their prevalence is experienced everywhere and cannot be considered as minor and neglected. Padadari (Crack Heel) is considered under Kshudra Roga (Minor ailments). Which is compared with cracked heels/heel fissures. Methods: In the present study, 30 subjects of Padadari (Crack Heel) were enrolled and treated with topical application of Sarjarasa Malahara (Sarjarasa Ointment). Results: After continuous application of Malahara (Ointment) from day 1st gradually cracks, it reduced from moderate to mild with significant result. Pharmacodynamics of ingredients were efficient in managing cracks. Discussion: Kshudra Rogas are mentioned in Ayurvedic texts as minor ailments which have cause of lower magnitude and have Lakshana (mostly local) of lower magnitude, which can be easily cured. Conclusion: The study yielded significant results in symptoms such as crack feet, pain. Ayurveda is the science of life which not only deals with the health and illness of human being but also considers the lifestyle and cosmetic aspects.[1] There is lot of difference between today’s life style and ancient lifestyle so Application of Ayurvedic principles need to be modified and applied according to disease condition. Ancient principles must be retestified because pure metal regains its shiny nature by its polishing. Ayurveda considers certain diseases under Kshudra Kushta. There are so many drugs in Ayurveda which prove effective against Kshudra Kushta like Tutha, Kapoor[2] etc. Many authors like Acharya Charaka, Acharya Sushruta, Acharya Vagbhata etc. mentioned few diseases under Kshudra Rogas.[3] Few authors kept